2012
DOI: 10.1098/rspb.2012.0842
|View full text |Cite
|
Sign up to set email alerts
|

Concessions of an alpha male? Cooperative defence and shared reproduction in multi-male primate groups

Abstract: By living in social groups with potential competitors, animals forgo monopolizing access to resources. Consequently, debate continues over how selection might favour sociality among competitors. For example, several models exist to account for the evolution of shared reproduction in groups. The 'concession model' hypothesizes that dominant reproducers benefit from the presence of subordinates, and hence tolerate some reproduction by subordinates. This mutual benefit to both dominants and subordinates may provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 51 publications
3
105
3
Order By: Relevance
“…Less attention has been paid to correlates of cooperation and fitness among primate males, for whom reproductive success is often more strongly correlated with dominance rank, which in turn is related to condition and fighting ability [26]. In recent years, however, it has become evident that the presence of allies can, in some instances, also influence the dominance ranks, tenure and reproductive success of primate males (Assamese macaques, Macaca assamensis [27]; Barbary macaques, Macaca sylvana [28]; geladas, Theropithecus gelada [29]). This observation also holds true for chimpanzees (Pan troglodytes [30,31]), whose male-bonded, fission -fusion society is very different from that of most Old World monkeys.…”
Section: The Adaptive Value Of Social Bondsmentioning
confidence: 99%
“…Less attention has been paid to correlates of cooperation and fitness among primate males, for whom reproductive success is often more strongly correlated with dominance rank, which in turn is related to condition and fighting ability [26]. In recent years, however, it has become evident that the presence of allies can, in some instances, also influence the dominance ranks, tenure and reproductive success of primate males (Assamese macaques, Macaca assamensis [27]; Barbary macaques, Macaca sylvana [28]; geladas, Theropithecus gelada [29]). This observation also holds true for chimpanzees (Pan troglodytes [30,31]), whose male-bonded, fission -fusion society is very different from that of most Old World monkeys.…”
Section: The Adaptive Value Of Social Bondsmentioning
confidence: 99%
“…By contrast, compromise models assume that reproductive skew is the outcome of a struggle over reproduction between group members, the intensity of which is mediated only by the detrimental effects it imposes on group productivity. Most studies of reproductive skew in mammalian societies have found support for compromise models or a less formalized class of models that focus on priority-of-access [35 -37] (but see [107,108]). …”
Section: (I) Social Organizationmentioning
confidence: 99%
“…Typically, males gain dominance through aggressive takeovers 32 , although other avenues have been suggested 33 . Although these units aggregate into large, highly concentrated herds that provide ample opportunity for extra-pair copulation (EPC) 34 , extra-unit paternity has never been documented 31 . However, some units have 1-5 subordinate 'follower' males that sire a small percentage (17%) of the unit's offspring 31 .…”
mentioning
confidence: 99%
“…Although these units aggregate into large, highly concentrated herds that provide ample opportunity for extra-pair copulation (EPC) 34 , extra-unit paternity has never been documented 31 . However, some units have 1-5 subordinate 'follower' males that sire a small percentage (17%) of the unit's offspring 31 . Despite taking away some reproduction from the leader male, follower males provide a net benefit to leaders through shared unit defence, and thus a longer tenure for the leader 31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation